A disciplina militar em sala de aula: a relação pedagógica em uma instituição formadora de oficiais da Polícia Militar do estado de São Paulo - Cerqueira, Homero de Giorge (2006)
The present work shows the process of formation of the officer of the Military Police of the State of São Paulo from the Academia de Polícia Militar do Barro Branco. Its main theme is the authoritarianism and the military discipline in the classroom. Theoretically supported by Michel Foucault s to Discipline and Punish: The Birth of the Prison my aim is to trace a historical panorama of the Military Police to understand this authoritarianism in the classroom. As a hypothesis, I put forward as a starting point for reasoning, the social-cultural evolution in which the responsible institution for the public order had to be inspired by human rights. When dealing with human rights and the dignity of the human being as regards the treatment of police officers as citizens, I have found out that there are evidences of equivocal authoritarianism in the formation of the military officer and I emphasize the idea of having a community police as a contribution to the solving of social conflicts. Consequently, I also propose the formation of officers at the military institutions and, simultaneously, at universities in order to promote the appearance of a hybrid formation of the police cadet adding to it the essence of the hierarchy and military discipline and that coming from the university. This movement will favour his maximum social inclusion, allowing him to solve his problems in a more democratic and humanistic way. Finally, I also take into consideration the curriculum of contemporaneity in which identity, the condition of the orther, diversity, subjectivity, signification and discourse, knowledge and power, knoweledge and culture are all interrelated in the formation of the officer of the Academilia de Polícia Militar do Barro Branco. I also point out thematic areas for implementation in the curriculum of the course in order to extinguish or minimize the authoritarianism in the classroom. Mediation and evaluation of the course are also pointed out as one of the most important aspects to improve the cadet s formation, transforming him into a responsible, democratic and autonomous officer